Subjet Multiplicities at LHC Energies and the QCD Color Factor Ratio CA/CF - M. Kaur; Anter P. Kaur (Advances in High Energy Physics)
Subjet multiplicity distributions of two jets with highest transverse momenta are simulated in proton-proton collisions at LHC energies of 7 TeV and 14 TeV. Jets are defined via the software package FastJet version 3.0.3 which includes the implementation of kT sequential recombination algorithm with a jet size of R=0.6. Subjets are resolved by rerunning the kT algorithm on the jets and using the resolution cutoff of ycut=10-3. The subjet multiplicity distributions and their average values are measured as a function of the jet momenta and upto rapidities η<2. The results are used to calculate the ratio, r=Mg-1/Mq-1.